Production and Characterization of TES-EPDM Foams With Paraffin for Thermal Management Applications - Valentini, Francesco; Fambri, Luca; Dorigato, Andrea; Pegoretti, Alessandro (Frontiers in Materials, 2021)
New materials able to store thermal energy in view of building applications have been developed from foaming ethylene-propylene diene monomer (EPDM) rubber and adding paraffin, as phase change material (PCM) with melting temperature at about 21°C. Considering that EPDM foams prepared using traditional chemical blowing agents are generally characterized by a rather elevated environmental load, the salt leaching technique has been selected (and optimized) for the production of EPDM foam with geometrical density of 0.41 g/cm3. TES-EPDM foams were able to retain up to 62 wt% of paraffin after 38 days of leaking test. The role of paraffin absorption on the thermal and mechanical properties of the produced foams has been investigated. The effective thermal energy of PCM content (PCMeff) measured through DSC was 52 % both in heating and cooling scan. Shore A, compression set and quasi static compression tests have been performed above and below the thermal transition of the selected PCM and a strong dependence respect to the testing temperature has been observed, with paraffin acting as hardener below its melting point and as softener above. Moreover, the evaluation of the thermal energy storage performance, carried out by monitoring of their surface temperature during heating/cooling process, revealed that the time required from the samples to reach the set temperature was three times higher in comparison to the reference EPDM foam. Moreover, during the plateau due to paraffin melting/crystallization, the heating/cooling rates have been found around 0.4 °C/min, much lower than reference sample (> 1.5 °C/min). The most accurate determination of thermal efficiency and thermal intervals for application of EPDM/paraffin has been therefore performed in DSC at heating/cooling rate of 1 °C/min. These TES-EPDM foams exhibited a thermal capacity of 120-128 J/g with an operative interval in the range -20 °C and 40°C. The produced foams were able to maintain their geometry after being subjected to 240 heating/cooling cycles between 0 and 40 °C, and their residual thermal energy storage capacity was higher than 90 % for all the samples . The most interesting properties for TES applications were found for produced via salt-leaching with 60-80 micron NaCl.